2004
DOI: 10.1164/rccm.200311-1499oc
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Toll-like Receptor 4 in Environmental Airway Injury in Mice

Abstract: Inhalation of toxins commonly found in air pollution contributes to the development and progression of asthma and environmental airway injury. In this study, we investigated the requirement of toll-like receptor 4 (TLR4) in mice for pulmonary responses to three environmental toxins: aerosolized lipopolysaccharide, particulate matter (residual oil fly ash), and ozone. The physiologic and biologic responses to these toxins were evaluated by the extent of airway responsiveness, neutrophil recruitment to the lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
143
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(154 citation statements)
references
References 48 publications
8
143
2
1
Order By: Relevance
“…Our study further sheds light on how a low dose of lung-sensitizing Ags such as LPS can facilitate tumor progression. Low levels of environmental LPS in inhaled air has been established to lead to latent chronic inflammation, which is deleterious for many pathologies that turn into a Th2-like immune environment (39)(40)(41). For example, asthma, which is characterized by a Th2-like environment (24), is exacerbated by low-dose LPS compared with high-dose LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Our study further sheds light on how a low dose of lung-sensitizing Ags such as LPS can facilitate tumor progression. Low levels of environmental LPS in inhaled air has been established to lead to latent chronic inflammation, which is deleterious for many pathologies that turn into a Th2-like immune environment (39)(40)(41). For example, asthma, which is characterized by a Th2-like environment (24), is exacerbated by low-dose LPS compared with high-dose LPS.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Despite a functioning airway defense such as mucociliary clearance, large fractions of fine and ultrafine PMs are capable of reaching the respiratory zone of the lungs. 40,41 In vitro and in vivo studies showed that PM exposure increases reactive oxygen species (ROS) formation and the number of proinflammatory markers in bronchoalveolar lavage. 40,41 This suggests that local proinflammatory processes and oxidative stress within the lungs are of relevance in the complex cascade that subsequently has deleterious systemic effects.…”
Section: Particulate Matter Causes Systemic Inflammationmentioning
confidence: 99%
“…via toll-like receptors and scavenger receptors. 41 Alveolar macrophages and dendritic cells recognize pathogenic patterns via toll- CI, confidence interval; IQR, interquartile range, lagx, days before onset or hospital admission; N, study population, 0.95 CI, 95%; OR, odds ratio; PMx, particulate matter with median aerodynamic diameter, RR, relative risk, *, result is statistically significant (P-valueo0.05). Search in Medline (PubMed search engine) 30, July 2013, search terms: all combinations of 'air pollution' , 'particulate matter' , and 'stroke' , 'ischemic stroke' .…”
Section: Particulate Matter Causes Systemic Inflammationmentioning
confidence: 99%
See 2 more Smart Citations